A New Procedure to Detect Low Interaction Honeypots - Eleazar Aguirre-Anaya; Gina Gallegos-Garcia; Nicolás Solano Luna; Luis Alfonso Villa Vargas (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Honeypots  systems  are   an   important  piece  of   the   network  security infrastructure and can be deployed to accomplish different purposes such as: network sensing, capturing and learning about 0-day exploits, capturing and analyzing of black hat techniques, deterring black hats and data gathering for doing  statistical  analysis  over  the  Internet  traffic,  among  others. Nevertheless, all honeypots need to look like real systems, due to if a honeypot is unmasked, it loses its value. This paper presents a new procedure to detect low interaction honeypots, through HTTP request, regardless honeypot architecture. It is important to mention that Low Interaction Honeypots network services need to be improved in order to get trustworthy information. Otherwise, it should consider data obtained by low interaction honeypots like inaccurate and unreliable information.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6885